Canidin-3-glucoside prevents nano-plastics induced toxicity via activating autophagy and promoting discharge. (1st April 2021) - Chen, Wen; Chu, Qiang; Ye, Xiang; Sun, Yuhao; Liu, Yangyang; Jia, Ruoyi; Li, Yonglu; Tu, Pengcheng; Tang, Qiong; Yu, Ting; Chen, Chuan; Zheng, Xiaodong
Abstract: Increasing attention has been brought to microplastics pollution recently, while emerging evidences indicate that nano-plastics degraded from microplastics are more of research significance owing to stronger toxicity. However, there is little study focused on the prevention of nano-plastics induced toxicity until now. Canidin-3-glucoside (C3G), a natural anthocyanin proved to possess multiple functions like antioxidant and intestinal tissue protection. Thus, we proposed whether C3G could act as a molecular weapon against nano-plastics induced toxicity. In Caco2 cell and Caenorhabditis elegans ( C. elegans ) models, we found that polystyrene (PS) nano-plastics exposure resulted in physiological toxicity and oxidative damage, which could be restored by C3G. More significantly in Caco2 cells, we observed that autophagy was activated via Sirt1-Foxo1 signaling pathway to attenuate PS induced toxicity after C3G intervention and further verified by adding autophagy inhibitor 3-Methyladenine (3-MA). Meanwhile, PS co-localization with lysosomes was observed, indicating the encapsulation and degradation of PS. In C. elegans, by detecting LGG-1/LC3 expression in GFP-targeted LGG-1 report gene (LGG-1:GFP) labeled transgenic DA2123 strain, the co-localization of LGG-1:GFP with PS was found as well, means that autophagy is involved in C3G's beneficial effects. Furthermore, we were surprised to find that C3G could promote the discharge of PS from N2 nematodes, which reduces PS toxicity more directly. Graphical abstract: Image 1 Highlights: C3G acts as a molecular weapon against nano-plastics induced toxicity. C3G promotes the discharge of nano-plastics in C. elegans. Autophagy is necessary for C3G to reduce nano-plastics induced toxicity.